ANALYSIS OF GRADUATE COMPETITIVENESS MANAGEMENT AND DEVELOPMENT STRATEGY OF PUBLIC VOCATIONAL HIGH SCHOOLS IN PALU CITY, CENTRAL SULAWESI PROVINCE - M, Rudin; Noval (Transpublika Publisher, 2021)
The purpose of this research is to find out and analyze the Competitiveness of Graduates of Public Vocational High School (SMK) 2 of Palu in Central Sulawesi Province as well as the Development Strategy. This type of research is qualitative research with informants selected as many as three people. Data collection uses observation, interview and documentation techniques. Data analysis techniques used are (1) Data collection (2) Data Reduction (3) Presentation of Data (4) Verification (5) Conclusions. According to the findings of the researchers' investigation and analysis, it was concluded that the competitiveness of graduates of Palu Public Vocational High School (SMK) 2 needs to be improved. This is obvious from the information presented during the study's informant interviews. Then there are graduates who remain jobless. Meanwhile, one could argue that the development strategy is acceptable. The footsteps of Palu's Public Vocational High School (SMK) 2, which sends instructors to the Master of Education level, demonstrate it well. Then, Palu Public Vocational High School (SMK) 2 collaborated or signed MOUs with 110 businesses in Central Sulawesi and other provinces.